2018
DOI: 10.5755/j01.mech.4.24.20721
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Indicators of a Corn Ear Threshing Process Influenced by the Threshing-Separation Unit Load

Abstract: Corn ear feed rate variations in the threshing-separation unit of a combine harvester have a significant impact on the dynamic indicators of the threshing process. In this study, we conducted experiments using a stationary tangential threshing device and measured the forces acting on the rear part of the concave as well as the torque of the rotating cylinder during a threshing process. The ThreshLab software was developed for this purpose. We found that increasing the corn ear feed rate made the threshing proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Under these conditions: broken rate 1.67 % and impurity rate 1.03 %. { BR = minimize IR = minimize 350 < X 1 < 450 35 < X 2 < 45 6 < X 3 < 8 (7) To verify the reliability of the regression model, the results were averaged over three trials of the above optimal threshing operation parameters, and the test results showed that the mean value of the broken rate was 1.74% and the mean value of the impurity rate was 0.98%. The relative error with the predicted value is less than 5%, which indicates that the accuracy of the regression model is high.…”
Section: Verification Experimentsmentioning
confidence: 99%
“…Under these conditions: broken rate 1.67 % and impurity rate 1.03 %. { BR = minimize IR = minimize 350 < X 1 < 450 35 < X 2 < 45 6 < X 3 < 8 (7) To verify the reliability of the regression model, the results were averaged over three trials of the above optimal threshing operation parameters, and the test results showed that the mean value of the broken rate was 1.74% and the mean value of the impurity rate was 0.98%. The relative error with the predicted value is less than 5%, which indicates that the accuracy of the regression model is high.…”
Section: Verification Experimentsmentioning
confidence: 99%
“…Many researchers have discovered that the feeding rate has a linear correlation with grain loss, machine power consumption, and other parameters [52][53][54]. To explore the influence of the feeding rate on the threshing effect of corn, Kiniulis V. et al [55,56] first designed three different structure filling plates installed on the threshing cylinder, and the feeding rate varied from 4 kg•s −1 to 12 kg•s −1 . It was suggested that an increase in the feed rate caused the threshing loss to increase.…”
Section: Effect Of Feeding Rate On Corn Threshingmentioning
confidence: 99%
“…It is assumed that when the ear contacts the threshing element, its velocity immediately changes and the impact behavior is random. If the ears pass through the area between the threshing cylinder and the concave at a constant velocity, then the times that threshing elements will impact on ears can be expressed as Equation (12).…”
Section: Model Of Rate Of Uncleared Grainmentioning
confidence: 99%
“…Li et al [10] designed a discrete roller model based on the discrete principle of rostrum bionic; the roller destroyed the arrangement rule of corn ears and loosened the corn grain, and the platform experiment indicated the optimal parameter combination. Kiniulis et al [11,12] studied the influence rules of threshing cylinder filler plates on the corn threshing process; cylinder rasp bars were designed and the test showed that the shape of spaces between rasp bars was related to ear threshing performance. Then, an influence model of working parameters on the corn feed rate during threshing was established, and test results showed that the force acting on the rear part of the concave tended to operate evenly at higher feed rates.…”
Section: Introductionmentioning
confidence: 99%